1984
DOI: 10.1159/000309371
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Experimental Intraocular Proliferation with Intravitreous 5-Fluouracil

Abstract: 5-Fluouracil, administered at concentrations of 1 and 5 mg to inhibit experimental intraocular proliferation produced by intravitreously implanted fibroblasts in rabbits, produced tissue alterations revealed by TEM. The degranulation and migration of pigment epithelial cells, the incipient degradation of axons and myelin sheets, the migration of glial cells and the prominent edema of the inner layers indicated a non-negligible damage to the retina, suggesting to abstain from its use in human eyes and to search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Binder and associates found that 25% of rabbit eyes receiving an intravitreal injection of 1 mg 5FU demonstrated narrowing of the retinal vessels and hemorrhage [2]. Kulnig demonstrated by transmission electron microscopy retinal damage in rabbit eyes following the intravitreal administration of 5FU in a 1-mg dose [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binder and associates found that 25% of rabbit eyes receiving an intravitreal injection of 1 mg 5FU demonstrated narrowing of the retinal vessels and hemorrhage [2]. Kulnig demonstrated by transmission electron microscopy retinal damage in rabbit eyes following the intravitreal administration of 5FU in a 1-mg dose [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic intraocular levels of 5FU can be achieved by intravitreal or subconjunctival administration [7]. However, frequent injections are needed to maintain therapeutic levels, and potentially toxic levels can occur immediately following an intravitreal injection of 1 mg into the rabbit eye [13,2]. A method that would increase the ocular penetration of a drug after subconjunctival injection, or slowly release the drug after intravitreal injection to increase its half-life, would be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…fixed and further processed for histologic and electron-microscopic examination [Kulnig et al, 1984).…”
Section: Histology and Electron Microscopymentioning
confidence: 99%
“…Antiproliferative preparations, such as dexamethasone alcohol, triamcinolone acetonide, 5-fluoracil and daunomicin, have proven their effectiveness in experimental conditions [Tano ct al., 1980;Binder, 1982;Blumenkranz et al, 1983: Binder et al, 1983Kulnig et al, 1984]. Their disadvantages, however, have also become manifest, as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Methylzellulose and Dexamethason Augentropfen erwiesen sich auch als symptomlindernde Therapie der Nebenwirkungen.5FU erwies sich als effektiver Inhibitor von Fibroblastenwachstum [62] and wird aufgrund dieser Eigenschaft auch bei chirurgischen Eingriffen in der Augenheilkunde verwendet. Es wurde sowohl intravitreal als auch subconjunctival an Tiermodellen injiziert um intraokulare Proliferationen zu inhibieren[63][64][65][66][67][68][69]. Seine lokale Gewebswirkung, kurze Halbwertszeit, leichte Administration and leichte Dosierbarkeit machten 5FU auch als Wundheilungshemmer in der Glaukomchirurgie beliebt…”
unclassified